Predicting heterosis via genetic distance and the number of SNPs in selected segments of chromosomes in maize - Jiang, Fuyan; Yin, XingFu; Li, Zi Wei; Guo, Ruijia; Wang, Jing; Fan, Jun; Zhang, Yudong; Kang, Manjit S.; Fan, Xingming (Frontiers in Plant Science, 2023)
A reliable method is needed for predicting heterosis to help maize (Zea mays L.) breeders develop new hybrids more efficiently. The objectives of this study were to 1) investigate if the numbers of selected PEUS SNPs (the SNP in the Promoters (1 kb upstream of the start codon), Exons, Untranslated region (UTR), and Stop codons) could be used for predicting MPH or BPH of GY; 2) if the number of PEUS SNPs is a better predictor of MPH and /or BPH of GY than genetic distance (GD). A line × tester experiment was conducted with 19 elite maize inbreds from three heterotic groups, which were crossed with five testers. The multi-location trial data on GY were recorded. Whole-genome resequencing of the 24 inbreds was carried out. After filtration, a total of 58,986,791 SNPs were called with high confidence. Selected SNPs in the promoters, exons, untranslated region (UTRs), and stop codons (PEUS SNPs) were counted, and the GD was calculated. The correlation between heterozygous PEUS SNPs/GD and mean MPH, BPH of GY revealed that 1) both the number of heterozygous PEUS SNP and the GD were highly correlated to both MPH_GY and BPH_GY at p<0.01 with correlation coefficients for the number of heterozygous PEUS SNP being higher than that for GD; 2) the mean number of heterozygous PEUS SNPs was also highly correlated with mean BPH_GY or mean MPH_GY (p<0.05) in the 95 crosses grouped by either male or female parents, implying that inbreds can be selected before making the actual crosses in the field. We concluded that the number of heterozygous PEUS SNPs would be a better predictor of MPH_GY and BPH_GY than GD. Hence, maize breeders could use heterozygous PEUS SNPs to select inbreds with high heterosis potential before actually making the crosses, thus improving the breeding efficiency.